Examining shared perceptions and awareness of gendered organisational political climates in male-dominated organisations: a power base model. - King, Michelle (Cranfield University, 2022)
Organisational politics and political behaviour are gendered, and this contributes to gender differences in building and maintaining power at work. This research utilises a systematic review to elicit mechanisms from the extant literature relating to organisational political climate (OPC) and power sources and their bases. Adopting semi-structured interviews and an abductive reasoning process, this research then examines how and why OPC and political behaviours are gendered by examining how power sources and bases are activated in two organisations (renamed EnergyCo and FinanceCo to ensure anonymity), where women make up less than 10% of senior positions at the time of undertaking the interviews. Examining how OPC and political behaviours are gendered within male-dominated organisations is important, as the gendered nature of these constructs is more likely to be heightened within this environment. The findings reveal that perceptions of OPC and political behaviours are gendered through the perceptions individuals form of the ideal worker, which is both gendered and political. The gendered nature of both OPC and political behaviours results in differential outcomes for men and women at work, reinforcing the gender power gap.
Keywords: Organisational politics; political behaviour; gender; gendered organisation; systematic literature review; perceptions